1985
DOI: 10.1161/01.cir.71.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of cardiac size: an echocardiographic and electrocardiographic study of monozygotic and dizygotic twins.

Abstract: Because of the uncertainty as to the extent to which cardiac size is determined by exercise training vs genetic endowment, this study investigated familial (genetic plus common family environment) vs nonfamilial influences on cardiac size. College-age monozygotic twins (group 1, 31 sets), dizygotic twins (group 2, 10 sets), siblings of like sex (group 3, six sets), and nonrelated subjects (group 4, 15 sets) underwent echocardiographic and electrocardiographic tests, measurement of maximum oxygen uptake (VO2max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 25 publications
1
33
0
1
Order By: Relevance
“…In the present analysis we did not examine the cross-trait intrafamilial relations between left ventricular mass and anthropometric characteristics. However, in keeping with the high heritability of anthropometric characteristics in twin studies, 34 we found sib-sib correlation coefficients of 0.52 for height and 0.30 for weight. We also noticed a significant concordance of height between spouses, which is likely to be due to by assortive mating.…”
Section: Discussionsupporting
confidence: 83%
“…In the present analysis we did not examine the cross-trait intrafamilial relations between left ventricular mass and anthropometric characteristics. However, in keeping with the high heritability of anthropometric characteristics in twin studies, 34 we found sib-sib correlation coefficients of 0.52 for height and 0.30 for weight. We also noticed a significant concordance of height between spouses, which is likely to be due to by assortive mating.…”
Section: Discussionsupporting
confidence: 83%
“…28 These data implicate a genetic predisposition in some with a strong family history of essential hypertension that may facilitate the development of cardiovascular changes at pressure loads that are borderline-elevated or of relatively short duration. Perhaps increased LVM in part is a phenotypic expression rather than a result of high blood pressure.…”
Section: Discussionmentioning
confidence: 91%
“…4 -8 Genetic influences on factors regulating myocardial growth or hemodynamics may be responsible for the etiology of increased mass, although information regarding the overall genetic influence on LV mass is limited. 4,8 The heritability (h 2 ) of heart size (P Ļ½ .002) in baboons is 0.39 and, in humans, falls between 0.22 and 0.59. 4,5,8 The LV remodels in response to physiologic stimuli (eg, increased peripheral vascular resistance, arterial stiffening, and plasma volume expansion), creating a variety of LV geometric phenotypes in hypertensive subjects.…”
mentioning
confidence: 99%